An Analysis of Politeness Maxims in the Movie “The Adventure of Tintin” - I Made Dwi Nova Muliartha; Ida Ayu Putri Gita Ardiantari (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study explored the types of politeness maxims that the main characters utilized and investigated the factors that influenced their use. The data were collected through focusing on observing main character specially "Tintin" interactions and circumstances during communication, with simultaneous notetaking to record pertinent instances of politeness maxims and use qualitative method. This methodology employs a data-driven approach, wherein data is initially gathered and subsequently analyzed to ascertain its relevance to a specific politeness maxim. Transcriptions were created based on the dialogues exchanged between the characters. In this study, analyze the politeness maxims observed in character interactions and dialogues within "The Adventure of Tintin." Drawing upon theories proposed by Leech, Holmes, and Wardaugh, reveal the tact and agreement maxims as the most frequently employed. This analysis demonstrates their significant role in shaping positive communication, character interactions, cultural nuances, and thematic elements within the film. Through meticulous examination, highlight the prevalence, influence, and contribution of these maxims to the narrative coherence and thematic depth of the movie